Direct bioconversion of sorghum extract sugars to free fatty acids using metabolically engineered Escherichia coli strains: Value addition to the sorghum bioenergy crop. (October 2016) - Bule, Mahesh; Luo, Yane; Bennett, George; Karanjikar, Mukund; Rooney, William; San, Ka-Yiu
Abstract: The unprecedented challenge of meeting the energy demand of growing economies has increased the need to produce hydrocarbon fuels using renewable sources. Among different platforms being researched these days, hydrocarbon biofuel and chemical production from free fatty acids (FFAs) have gained a lot of attention. The current study reports on value addition to sorghum energy crop through utilization of sorghum extract as a renewable carbon source for FFA production using genetically engineered Escherichia coli . In order to reduce the production cost of FFAs, direct sucrose utilizing E. coli strains were developed. The E. coli strain MG1655 with fadD mutant (named as ML103) either carrying the plasmid bearing the gene for acyl-ACP thioesterase (TE) from Ricinus communis (pXZ18) or a plasmid bearing a combination of the TE and the native (3R)-hydroxyacyl-ACP dehydrase gene ( fabZ ) (pXZ18Z) was modified to utilize sucrose by incorporating the pUR400 plasmid. The newly created strains utilized a mixture of pure sugars and sorghum extract efficiently. The 24 h pH adjusted culture of ML103 pXZ18Z pUR400 produced a maximum of 6.18 ± 0.52 g l −1 from 30 g l −1 of pure sugar mixture and 2.95 ± 0.04 g l −1 with sorghum extract (15 g l −1 equivalent sugar concentration). These data suggest that modified E. coli strains were capable of directly utilizing sucrose and produce FFAs from it. Successful demonstration of direct bioconversion of sorghum extract to FFA was validated as a possible value addition of the sorghum bioenergy crop. Graphical abstract: Highlights: Escherichia coli strain was successfully modified for direct sucrose utilization and for the of production free fatty acids. Recombinant E. coli strains can make fatty acids from sorghum extracts and from pure sugars with comparable efficiency. Sorghum extract successfully utilized as a carbon source for free fatty acid production. Fermentation culture pH manipulation improved free fatty acid production significantly while decreasing acetate formation.